LapG mediates biofilm dispersal in Vibrio fischeri by controlling maintenance of the VCBS-containing adhesin LapV - Christensen, David G. (Mol Microbiol, 2020)
Efficient symbiotic colonization of the squid Euprymna scolopes by the bacterium Vibrio fischeri depends on bacterial biofilm formation on the surface of the squid’s light organ. Subsequently, the bacteria disperse from the biofilm via an unknown mechanism and enter through pores to reach interior colonization sites. Here, we identify a homolog of Pseudomonas fluorescens LapG as a dispersal factor that promotes cleavage of a biofilm-promoting adhesin, LapV. Overproduction of LapG inhibited biofilm formation and, unlike the wild-type parent, a ΔlapG mutant formed biofilms in vitro. Although V. fischeri encodes two putative large adhesins, LapI (near lapG on chromosome II) and LapV (on chromosome I), only the latter contributed to biofilm formation. Consistent with the Pseudomonas Lap system model, our data support a role for the predicted c-di-GMP-binding protein LapD in inhibiting LapG-dependent dispersal. Furthermore, we identified a phosphodiesterase, PdeV, whose loss promotes biofilm formation similar to that of the ΔlapG mutant and dependent on both LapD and LapV. Finally, we found a minor defect for a ΔlapD mutant in initiating squid colonization, indicating a role for the Lap system in a relevant environmental niche. Together, these data reveal new factors and provide important insights into biofilm dispersal by V. fischeri.